Waist circumference measures and application to thai children and adolescents - Uruwan Yamborisut (2018)
© Springer Science+Business Media, LLC 2012. All rights reserved. The prevalence of childhood obesity has been increasing worldwide. Assessment of changing trends in nutritional and health status of the child population could be achieved using accurate and reliable body composition techniques. Waist circumference is a simple anthropometric measure that is useful for the detection of abdominal obesity which reflects the sum of subcutaneous and visceral adipose tissues in the trunk region. Research evidence shows that waist circumference is highly correlated with weight-for-height and body mass index. Waist circumference is also a good predictor of cardiovascular risk factors. Measurement of waist circumference can be performed at different sites of the trunk region and the measurement technique requires a standardized procedure. Reference data of percentile distributions of waist circumference among children and adolescents are now available in many countries, including Thailand. Waist circumference cut-off can be an advantageous tool for a large-scale screening of children who are at risk for overnutrition and for tracking child growth. Future studies need to address the universal waist circumference benchmark and the application of waist circumference as well as weight-to-height ratio for growth monitoring and public health intervention program towards promoting a healthy child population.